Study of Poisoning Cases in a Tertiary Care Hospital - Karki, RK; Risal, A (Kathmandu University Medical Journal, 2014)
Background Poisoning is one of the leading causes of morbidity and mortality in Nepal and also a major public health problem worldwide. A thorough review of the risk factors helps to decrease the incidence and mortality. The study evaluates the cases admitted in Dhulikhel Hospital, Kavre, Various parameters like age, sex, marital status, time of ingestion, month of occurrence, agent responsible for incidence; type of poisoning, psychosocial problem, outcome and duration of treatment are analyzed. Objectives The objectives of this study are to determine the pattern and severity of poisoning cases admitted to Dhulikhel Hospital. Methods A hospital based study was carried out in the patient admitted to Dhulikhel Hospital with the history of poisoning for the period of one year between April 2011 to March 2012. Various parameters were analyzed and compared with other study. Results There were 137 cases during the one year duration and maximum case belonged to second and third decade of life. Most common manner of poisoning was suicidal and the incidence was mainly during evening hours. Organophosphorus was the most commonly abused substance. Most of the cases had arrived hospital after one hour of exposure and duration of hospital stay in many cases were less than four days. Conclusion Based on these findings preventive measures like precaution taken at various levels, restriction in free sale of the poisons and promoting Poison Information Centers along with public awareness and proper psychosocial management to decrease the incidence and mortality in poisoning cases can be suggested. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10999 Kathmandu Univ Med J 2012;10(4):70-73